The Relationship of Age and Body Mass Index with Histopathological Features of Breast Carcinoma at RSUD Abdul Wahab Sjahranie Samarinda - Ihza Firdaus, Ajril; Irawiraman, Hadi; Riastiti, Yudanti (Fakultas Kedokteran, 2024)
Background : Breast carcinoma is a disease characterized by the uncontrolled growth of breast epitel cells. Breast carcinoma is the most common cancer in the world and Indonesia. Breast cancer is caused by many factors, including age and obesity. Aim : This study aims to explain the relationship between age and body mass index with histopathological features of breast carcinoma at Abdul Wahab Sjahranie Hospital Samarinda. Methods : An analytical observational study with a cross-sectional approach was applied in this study. The research sample was taken from the anatomical pathology laboratory and medical record installation at Abdul Wahab Sjahranie Hospital Samarinda with a purposive sampling method. One hundred fifty-one samples were obtained from all breast cancer patients diagnosed histopathologically at RSUD Abdul Wahab Sjahranie Samarinda from the period 2020-2021 for this study. The data in this study were tested using the Chi-Square test. Result : The results showed that the analysis between age with histopathological type and grading of breast carcinoma, respectively, obtained p-value = 0.129 and p-value = 0.174, while BMI with histopathological type and grading of breast carcinoma obtained p-value = 0.467 and p-value = 0.199. Conclusion : There was no relationship between age and body mass index with histopathological features of breast carcinoma.